swift biometries - Morganti, Michelangelo; Rubolini, D.; Bermejo, Ana; De La Puente, Javier; Boano, Giovanni; Tomassetto, Erika; Ferri, Mauro; Caffi, Mario; Saino, Nicola; Ambrosini, Roberto (Dryad Digital Repository, 2017)
file containing measures of wing and weight of Apus apus and Apus pallidus from the study sites for which these were available.